The role of growth hormone in assisted reproductive technology for patients with diminished ovarian reserve: from signaling pathways to clinical applications - Han, Peina; Xu, Huishu; Yuan, Yuying; Wen, Zheling; Yang, Jing; Han, Lei; Zhang, Dongmei (Frontiers in Endocrinology, 2025)
Diminished Ovarian Reserve (DOR) is a complex etiology disease that significantly impacts female fertility, endocrine function, and overall health status. In recent years, the incidence of DOR has been increasing, yet therapeutic methods remain relatively limited, particularly for patients with reproductive needs who often require Assisted Reproductive Technology (ART) treatments. Growth Hormone (GH), a peptide hormone secreted by the anterior pituitary, promotes growth in bones, viscera, and multiple organs and systems throughout the body, enhances protein synthesis, and influences fat and mineral metabolism, playing a crucial role in human growth and development. Its levels decrease with the aging of the organism. In recent years, studies have suggested that a decline in growth hormone levels may be one of the causes of decreased ovarian function, leading to the application of GH in assisted reproductive treatments for patients with DOR. An increasing body of research indicates that GH can improve ovarian function through mechanisms such as antioxidant stress, promotion of follicle development, and enhancement of oocyte quality, and it also shows potential to improve endometrial receptivity, making GH a promising safe and effective strategy in ART for DOR patients.